2016
DOI: 10.1007/s10886-016-0794-8
|View full text |Cite
|
Sign up to set email alerts
|

Emission of Volatile Compounds from Apple Plants Infested with Pandemis heparana Larvae, Antennal Response of Conspecific Adults, and Preliminary Field Trial

Abstract: This study investigated the volatile emission from apple (Malus x domestica Borkh., cv. Golden Delicious) foliage that was either intact, mechanically-damaged, or exposed to larval feeding by Pandemis heparana (Denis and Schiffermüller) (Lepidoptera: Tortricidae). Volatiles were collected by closed-loop-stripping-analysis and characterized by gas chromatography-mass spectrometry in three time periods: after 1 h and again 24 and 48 h later. Volatiles for all treatments also were monitored continuously over a 72… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
72
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 35 publications
(84 citation statements)
references
References 81 publications
8
72
1
Order By: Relevance
“…The experiment with rubber septa lures clearly showed that 2-phenylethanol alone is an ineffective attractant of P. limitata, whereas acetic acid appeared weakly attractive as it is for several tortricid species (Knight et al 2014). These results are consistent with European studies showing that 2-phenylethanol was not attractive to Pandemis species when used alone (Giacomuzzi et al 2016). However, unlike Pandemis species in the European study (Giacomuzzi et al 2016), P. limitata moths were caught significantly more often with acetic acid + 2-phenylethanol than they were with acetic acid + phenylacetonitrile.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The experiment with rubber septa lures clearly showed that 2-phenylethanol alone is an ineffective attractant of P. limitata, whereas acetic acid appeared weakly attractive as it is for several tortricid species (Knight et al 2014). These results are consistent with European studies showing that 2-phenylethanol was not attractive to Pandemis species when used alone (Giacomuzzi et al 2016). However, unlike Pandemis species in the European study (Giacomuzzi et al 2016), P. limitata moths were caught significantly more often with acetic acid + 2-phenylethanol than they were with acetic acid + phenylacetonitrile.…”
Section: Discussionsupporting
confidence: 83%
“…European studies have thoroughly characterised the volatiles released by apple leaves in response to larval feeding by Pandemis heparana Denis and Schiffermüller (Giacomuzzi 2010;Giacomuzzi et al 2013Giacomuzzi et al , 2016. Among the many compounds emitted by apple leaves, six were considered unique and only released in response to herbivory.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Monitoring adult tortricid pests with traps is a key component of deciduous tree fruit management (Witzgall, Kirsch, & Cork, ). Sex pheromone lures have primarily been used to monitor males of these species, and more recently bisexual kairomonal attractants have been developed for the key tortricid pests (Giacomuzzi et al., ; Knight et al., ; Light et al., ). While a few studies have suggested that male captures in traps baited with kairomones could be influenced by previous female captures, this factor has not previously been evaluated experimentally.…”
Section: Discussionmentioning
confidence: 99%
“…An increasing body of research has developed bisexual attractants for key tortricid pests of apple Malus domestica Borkhausen, using host plant volatiles and/or microbial‐based compounds (codling moth: Light et al., ; Landolt, Suckling, & Judd, ; Landolt et al., ; leaf rollers: Giacomuzzi et al., ; Giacomuzzi, Mattheis, Basoalto, Angeli, & Knight, ; Judd, Knight, & El‐Sayed, 2017a, 2017b; Basoalto et al., ; oriental fruit moth: Mujica et al., ). The ability of pest managers to monitor female moth populations can increase the precision in tracking the pest phenology and improve timing of control tactics (Knight & Light, 2005a).…”
Section: Introductionmentioning
confidence: 99%